2019
DOI: 10.1371/journal.pone.0210513
|View full text |Cite
|
Sign up to set email alerts
|

Propyl gallate inhibits hepatocellular carcinoma cell growth through the induction of ROS and the activation of autophagy

Abstract: The poor prognosis of hepatocellular carcinoma (HCC) has been attributed to a high frequency of tumor metastasis and recurrence even after successful surgical resection. With less than 30% of patients benefiting from curative treatment, alternative treatment regimens for patients with advanced HCC are needed. Propyl gallate (PG), a synthetic antioxidant used in preserving food and medicinal preparations, has been shown to induce cancer cell death, but the anticancer effects of PG in HCC are unclear. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 63 publications
(65 reference statements)
2
35
0
Order By: Relevance
“…For nondigested extracts, the impact on yeast cells was the opposite of that observed for digested extracts, i.e., a decreased stress resistance was observed suggesting a disturbed defence against oxidative stress. This suggestion agrees with the findings reported by Wei et al [ 36 ]. They showed that in human cells the phenolic propyl gallate, synthesized by the condensation of gallic acid and propanol, might, in certain conditions, increase the levels of reactive oxygen species (ROS) and/or promote depletion of protective enzymes or glutathione.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…For nondigested extracts, the impact on yeast cells was the opposite of that observed for digested extracts, i.e., a decreased stress resistance was observed suggesting a disturbed defence against oxidative stress. This suggestion agrees with the findings reported by Wei et al [ 36 ]. They showed that in human cells the phenolic propyl gallate, synthesized by the condensation of gallic acid and propanol, might, in certain conditions, increase the levels of reactive oxygen species (ROS) and/or promote depletion of protective enzymes or glutathione.…”
Section: Discussionsupporting
confidence: 94%
“…The health benefits of anthocyanins are commonly suggested to originate from their antioxidant and anti-inflammatory activities related to their chemical structure [ 35 ]. However, epigenetic activities have also been associated with flavonoids, which seem to induce changes in gene expression protecting, for example, against cancer [ 36 ]. The mechanisms of cell protection by polyphenols are not fully understood, and neither is the relative degree of protection by intact anthocyanins versus their derivatives resulting from GI-digestion.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies have used a total ROS detection kit for the measurement of ROS and SO in triple negative breast cancer cell lines, colon cancer cells, colorectal cancer cell lines, and in hepatocellular carcinoma cells [17,18,19,20,21]. We used the same ROS-ID Total ROS/SO detection kit (Enzo Life Sciences, Farmingdale, NY, USA) to measure fluorescence due to ROS/SO production following manufacturer’s protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy inhibitors also foster apoptotic cell death triggered by bevacizumab in the presence of ROS derived from starvation or hypoxia [77]. The occurrence of apoptotic cell death after salinomycin, capsaicin, propyl gallate, or licochalcone A treatment was instead dependent on a direct impact of these molecules on the autophagic response to oxidative stress [7881] (Table 2).…”
Section: Autophagic Response To Oxidative Stress During Hcc Therapmentioning
confidence: 99%